Ancient role of vasopressin/oxytocin-type neuropeptides as regulators of feeding revealed in an echinoderm - Esther A. Odekunle; Dean C. Semmens; Nataly Martynyuk; Ana B. Tinoco; Abdullah K. Garewal; Radhika R. Patel; Liisa M. Blowes; Meet Zandawala; Jérôme Delroisse; Susan E. Slade; James H. Scrivens; Michaela Egertová; et al. (BMC Biology, 2019)
Abstract Background Vasopressin/oxytocin (VP/OT)-type neuropeptides are well known for their roles as regulators of diuresis, reproductive physiology and social behaviour. However, our knowledge of their functions is largely based on findings from studies on vertebrates and selected protostomian invertebrates. Little is known about the roles of VP/OT-type neuropeptides in deuterostomian invertebrates, which are more closely related to vertebrates than protostomes. Results Here, we have identified and functionally characterised a VP/OT-type signalling system comprising the neuropeptide asterotocin and its cognate G-protein coupled receptor in the starfish (sea star) Asterias rubens, a deuterostomian invertebrate belonging to the phylum Echinodermata. Analysis of the distribution of asterotocin and the asterotocin receptor in A. rubens using mRNA in situ hybridisation and immunohistochemistry revealed expression in the central nervous system (radial nerve cords and circumoral nerve ring), the digestive system (including the cardiac stomach) and the body wall and associated appendages. Informed by the anatomy of asterotocin signalling, in vitro pharmacological experiments revealed that asterotocin acts as a muscle relaxant in starfish, contrasting with the myotropic actions of VP/OT-type neuropeptides in vertebrates. Furthermore, in vivo injection of asterotocin had a striking effect on starfish behaviour—triggering fictive feeding where eversion of the cardiac stomach and changes in body posture resemble the unusual extra-oral feeding behaviour of starfish. Conclusions We provide a comprehensive characterisation of VP/OT-type signalling in an echinoderm, including a detailed anatomical analysis of the expression of both the VP/OT-type neuropeptide asterotocin and its cognate receptor. Our discovery that asterotocin triggers fictive feeding in starfish provides important new evidence of an evolutionarily ancient role of VP/OT-type neuropeptides as regulators of feeding in animals.